Kinerja Keuangan Bank Mega dan Bank Mega Syariah Menggunakan Pendekatan Camel - Uswah, Rosyida; Arif, Yulia (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research aims to compare the financial performance between Bank Mega and Bank Mega Syariah during the 2018-2022 period using the CAMEL approach. The research method used is descriptive comparative through a quantitative approach. The data used are Bank Mega and Bank Mega Syariah quarterly reports for the 2018-2022 period. The results of descriptive statistical tests show that the majority of the financial ratios of the two banks are in the good or very good category based on applicable standards. However, the results of hypothesis testing using the Mann-Whitney U Test indicate that there are significant differences in financial performance between the two banks. Bank Mega has better performance in terms of CAR, ROA, BOPO and LDR ratios, while there is no significant difference in the NPL ratio between the two banks.